Adherence to Anti-Seizure Medications in Children with Epilepsy Attending a Tertiary Care Center in Bangladesh (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2023)
Background: Epilepsy is one of the most common neurological morbidities in children worldwide. Anti-Seizure Medication (ASM) is the mainstay of epilepsy treatment. Adherence to Anti-Seizure Medication (ASM) is the key to achieving seizure remission. So this study aimed to assess the adherence to anti-seizure medication among children with epilepsy and to identify the factors that influence adherence.Materials and methods: It was a cross-sectional study involving Infants and children aged six months to twelve years old with seizure disorder irrespective of etiology, taking anti-seizure medications for more than six months and receiving mono or polytherapy were enrolled as the study subject. Self-reporting measures were used to assess adherence. Patients' caregivers were interviewed for the assessment of adherence. Descriptive statistical analysis was used to analyze the data, and univariate analysis with a chi-square test was used to observe the association between the variables and adherence.Results: The mean±SD age of the participants was 34.75 ± 38.39 months. A significant association was found between the age of the respondent and compliance with anti-seizure medication (30.5± 27.25 vs. 39.99±36.67 months p=0.012). Males were more than females 28(70%) Vs. 12(30%). Most of the study subjects were belonging to lower-middle-class families 13(33.3%). The generalized onset of seizure was the frequent type of seizure 28(70%). The majority of the participants 24 (60%) did have a seizure with structural etiology. Most of the study subjects received monotherapy 34(85%). Sodium valproate 19(47.5%) was the most frequently used drug. Seizure remission was found in 28(70%) of the study population. No significant association was found between the treatment outcome and adherence to antiseizure medication (ASM). Adherence to ASM was found in 55% of this study. Unable to afford cost was found to be the main cause of non-adherence 14(35%). There is a significant association found between the duration of taking ASM and compliance with ASM (7.05 ± 5.3 vs. 17.56± 15.43 months p=0.005).Conclusion: Adherence to Anti-Seizure Medication (ASM) is low in our study. Unable to afford cost was the main factor accountable for non-adherence appropriate interventions are needed to improve ASM compliance and consequently treatment outcome.Chatt Maa Shi Hosp Med Coll J; Vol.22 (1); January 2023; Page 38-43